Modelling total phosphorus input pathways in the Porsuk reservoir catchment in Turkey - Celen, Meltem; Karpuzcu, Mehmet; Engin, Guleda Onkal; Tetzlaff, Bjoern; Wendland, Frank (SPRINGER, 2014)
As a country in the Mediterranean region, Turkey must face the effects of climate change on water quality and quantity. Decision support systems are accepted as useful and practical tools for the protection and management of water resources. The need for such tools is rapidly emerging in conjunction with industrial developments in Turkey. Against this background, the empirical area-differentiated phosphorus model MEPhos developed for the mid-European site conditions was transferred and adapted for a representative study area in Turkey, the Porsuk reservoir catchment. Adaption included the development of a model approach to consider the P input into surface waters from septic tanks. For this purpose, several field campaigns were carried out to define characteristic P emission coefficients for septic tanks. In addition, the soil phosphorus content of the top soil was defined to generate reliable input data for the modelling of the P input into surface water via soil erosion in agricultural areas. According to the MEPhos model results, mean annual phosphorous loads of all types of point sources dominate with a percentage of around 57 %. Erosion contributes to 40 % of the total P load and displays the most significant diffuse input pathway. The validation studies conducted between 2007 and 2011 showed a satisfying agreement with the observed values. After validation, the efficiency of measures to reduce P inputs into the Porsuk reservoir was analysed. It was found that most measures to prevent soil erosion seem to be appropriate, whereas measures to reduce P input from point sources seem to be less efficient.
Keywords: Total phosphorus; Point sources; Diffuse sources; Pollution prevention scenarios; Porsuk reservoir catchment